Sierra Leone Public Expenditure Review 2021 : Improving Quality of Public Expenditure in Health - World Bank (World Bank, Washington, DC, 2021)
Sierra Leone is a low-income, small West African country of approximately 7.65 million population. Over the past decade, the country has made gains on several health indicators, but it faces huge challenges. Infectious diseases remain the leading causes of morbidity and mortality, but non-communicable diseases appear to be trending upward. Critical skills and competencies in public financial management, procurement, and monitoring and evaluation (M&E) require strengthening to deliver health improvements. The objective of this Public Expenditure Review (PER) was to assess public expenditure on health to inform policymakers of the effectiveness, efficiency, and equity of health expenditures in Sierra Leone.